Blockchains and the Civic Nervous System - Alessandro Voto (Field Actions Science Reports, 2017)
In this article, Alessandro Voto takes us on a journey to explore how the rise of Blockchains protocol will transform city management enabling more distributed city governance and the emergence of a range of new urban services where machines and humans collaborate in new ways to store, move and transact. Projected to operate at a fraction of the cost of centralized protocols, those new services will be particularly adapted to underserved populations by providing mobile and secure identity for them and the value that they create.